Sistem Saraf Otonom (SSO) - Mu’tia Aulia Ramadhani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The Autonomic Nervous System (ANS) is a part of the peripheral nervous system that plays a role in controlling bodily functions unconsciously. The ANS consists of two main divisions, namely the sympathetic and parasympathetic nervous systems, which work antagonistically to maintain the body's homeostasis. This article discusses the structure, function, and working mechanisms of the ANS under various physiological and pathological conditions. Understanding the ANS is crucial in the medical field, especially in managing diseases related to autonomic nervous system dysfunction.